Hubungan Pengetahuan dan Tindakan Menjaga Kesehatan Gigi Mulut dengan Keluhan Subyektif Permasalahan Gigi Mulut pada Mahasiswa Kesehatan dan Non Kesehatan - Rahmadani, Nanang; Udin, Priti Sinta; Mu’minina, Nur; Zulkarnain, Zulkarnain; AR, Aisyah; Wijaya, Ayu (Jurnal Ilmiah Amanah Akademika, 2021)
Individual behavior related to oral health could cause poor oral condition. Health behavior consists of domains of knowledge, attitude, and action related to health, including oral health. This study was aimed to evaluate the relationship between knowledge and action to maintain oral health and subjective complaints related to oral condition of medical and non-medical students. This was an analytical and observational study with a cross sectional design. Samples were medical and non- medical students obtained by using the consecutive sampling technique. Data were collected at Muslim Islamic University using online questionnaire through the Google form platform regarding knowledge, actions to maintain oral health, and subjective complaints of oral health problems. Data were analyzed by using the chi-square test. The results showed that the majority of students had a high level of knowledge about dental and oral health, meanwhile, their action to maintain oral health was in moderate level. The levels of knowledge and action to maintain oral health of medical students were better than of the non-medical students. Dental and oral health problems most frequently complained were recurrent aphtous ulcers (RAU) and dental caries. The chi-square test showed a p-value of 0.023 between the action to maintain oral health and subjective complaints of oral health problems. In conclusion, there was a significant relationship between the action to maintain oral health and subjective complaints of oral health problems.